2022
DOI: 10.1177/00936502211062773
|View full text |Cite
|
Sign up to set email alerts
|

Is Constructive Engagement Online a Lost Cause? Toxic Outrage in Online User Comments Across Democratic Political Systems and Discussion Arenas

Abstract: This study is the first to simultaneously investigate country-level and platform-related context factors of toxic outrage, that is, destructive incivility, in online discussions. It compares user comments on the public role of religion and secularism from 2015/16 in four democracies (Australia, United States, Germany, Switzerland) and four discussion arenas on three platforms (News websites, Facebook, Twitter). A novel automated content analysis ( N = 1,236,551) combines LIWC dictionaries with machine learning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…However, further dimensions could be included in the definition of debate quality. For instance, Jakob et al (2022) assessed how the political system of a country and the type of discussion arena (namely, blog posts, Facebook posts and tweets) condition toxic outrage online as a violation of civility norms. Debate quality could also be supplemented by the analysis of argument quality (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, further dimensions could be included in the definition of debate quality. For instance, Jakob et al (2022) assessed how the political system of a country and the type of discussion arena (namely, blog posts, Facebook posts and tweets) condition toxic outrage online as a violation of civility norms. Debate quality could also be supplemented by the analysis of argument quality (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning the realm of social media, Brundidge et al (2014) showed that conservative bloggers were less integrative than liberal bloggers, thus highlighting the risk of a potential exacerbation of divisions in cognitive-linguistic styles on polarised political blogs. On a contextual level, Jakob et al (2022) showed that toxic outrage depends on the type of democratic system , and that it is mainly higher in majoritarian democracies than in consensus-oriented democracies and in arenas that afford plural and issue-driven, rather than like-minded and preference-driven, debates. From the broader perspective of democratic deliberation, there are additional factors worth considering that can impact on the quality of political debate.…”
Section: Study Backgroundmentioning
confidence: 99%
“…Cross-national examinations are powerful insofar as they consider regulatory practices, cultural norms, journalistic cultures, media systems, and political contexts [61]. For instance, one analysis revealed higher toxic outrage in comments in majoritarian democracies compared to consensus-oriented ones [86].…”
Section: User-driven Toxicity: Who Are the Uncivil Users?mentioning
confidence: 99%
“…For instance, in the field of journalism studies, Stoll et al (2020) test and compare different SML techniques to predict impoliteness and incivility in online discussions on German news media outlets on Facebook. More recently, Jakob et al (2022) combined LIWC dictionaries with machine learning to study destructive incivility in online user comments on news websites, Facebook, and Twitter.…”
Section: Previous Research Based On Automated Content Analyses Of Use...mentioning
confidence: 99%